A negative electrode sheet, a solid-state battery comprising the same, and a smart terminal comprising the solid-state battery
Patent Information
- Application Number
- CN202610984609.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-23
AI Technical Summary
在全固态电池的刚性堆叠结构中,这种剧烈的体积变化缺乏缓冲空间,极易造成电极内部裂纹扩展、活性物质与固态电解质层剥离,导致离子/电子传输网络断裂
[0027]本公开实施例提供的技术方案与现有技术相比具有如下优点:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of secondary battery technology, and more particularly to a negative electrode sheet, a solid-state battery comprising the same, and a smart terminal comprising the solid-state battery. Background Technology
[0002] All-solid-state lithium batteries are considered a core development direction for next-generation energy storage technology due to their high safety and potential high energy density. Among various solid-state electrolyte systems, sulfide solid-state electrolytes stand out for their excellent room-temperature ionic conductivity (up to 10⁻⁶ Ω·cm). -3 ~10 -2 With its S / cm scale, good interfacial wettability, and wide stability window, it is widely regarded as one of the most promising material systems for realizing the commercialization of all-solid-state batteries.
[0003] Elemental silicon (Si) has a theoretical specific capacity of up to 4200 mAh / g, which is more than ten times that of traditional graphite anodes (372 mAh / g). It is a key anode material to match high-nickel cathodes in order to achieve an energy density target of over 400 Wh / kg.
[0004] However, when silicon-based anode materials are applied to sulfide solid-state battery systems, the physicochemical incompatibility between the two is extremely prominent, severely limiting the cycle life and rate performance of all-solid-state batteries. Specifically, this manifests in the following ways: First, volume effects lead to structural failure. Silicon-based materials undergo volume expansion of up to 300% during charging and discharging. In the rigid stacked structure of all-solid-state batteries, this drastic volume change lacks buffer space, making it highly susceptible to crack propagation inside the electrodes, peeling of the active material from the solid electrolyte layer, and breakage of the ion / electron transport network.
[0005] Second, it is difficult to balance the overall electrochemical performance. Existing anode structures are difficult to balance high capacity and fast charging performance. When the proportion of silicon-based materials is high, the high capacity requirement can be met, but the low transport rate of silicon ions leads to a decrease in rate performance.
[0006] Furthermore, in traditional negative electrode structures, the active material near the current collector has a longer ion transport path and a significant lithium ion concentration gradient, resulting in uneven utilization of the deep active material.
[0007] To address the aforementioned technical issues, CN121394361A discloses a negative electrode material for sulfide solid electrolyte batteries, which employs a polymer-coated silicon-carbon composite material. However, this method still suffers from the following drawbacks: 1. The polymer coating layer increases interfacial impedance and reduces ion transport efficiency; 2. The coating process is complex and costly; 3. The polymer exhibits poor long-term cycling stability and is prone to degradation; 4. The polymer material has poor compatibility in sulfide electrolyte systems; 5. Rate performance is limited, making it difficult to achieve rapid charge and discharge.
[0008] CN121687855A discloses a negative electrode sheet, its preparation method, and a solid-state battery. A first coating layer is formed on the surface of a current collector, and a second coating layer is formed on the surface of the first coating layer. The first coating layer comprises a silicon / lithium-silicon composite material, and the second coating layer comprises a pre-lithiated silicon-carbon material. However, this method still has the following drawbacks: 1. Abrupt compositional changes between the two layers lead to interfacial stress concentration, which can easily cause interlayer separation; 2. The risk of side reactions between the silicon / lithium-silicon material and the sulfide electrolyte is high.
[0009] In summary, how to alleviate the volume expansion problem of silicon-based materials in all-solid-state batteries, optimize ion transport channels, and balance high capacity and fast charging performance have become urgent technical challenges to be solved in this field. Summary of the Invention
[0010] To address the aforementioned technical problems, this disclosure provides a negative electrode sheet, a solid-state battery comprising the same, and a smart terminal comprising the solid-state battery.
[0011] In a first aspect, this disclosure provides a negative electrode sheet, including a negative electrode current collector, a first negative electrode active material layer disposed on at least one side of the negative electrode current collector, and a second negative electrode active material layer disposed on the side of the first negative electrode active material layer away from the negative electrode current collector. The first negative electrode active material layer includes a first solid electrolyte, a first negative electrode active material, a first conductive agent, and a first binder; the first negative electrode active material includes a first silicon-based material; The second negative electrode active material layer includes a second solid electrolyte, a second negative electrode active material, a second conductive agent, and a second binder; the second negative electrode active material includes a second silicon-based material and a second carbon-based material. The mass percentage of the first silicon-based material in the first negative electrode active material is greater than the mass percentage of the second silicon-based material in the second negative electrode active material.
[0012] As a preferred technical solution of this disclosure, the first negative electrode active material further includes a first carbon-based material.
[0013] As a preferred technical solution of this disclosure, the first carbon-based material and the second carbon-based material each independently include graphite.
[0014] As a preferred technical solution of this disclosure, the mass content of the first solid electrolyte in the first negative electrode active material layer is less than or equal to the mass content of the second solid electrolyte in the second negative electrode active material layer.
[0015] As a preferred technical solution of this disclosure, the difference between the mass content of the second solid electrolyte in the second negative electrode active material layer and the mass content of the first solid electrolyte in the first negative electrode active material layer is 0-25%.
[0016] As a preferred technical solution of this disclosure, the difference between the mass percentage of the first silicon-based material in the first negative electrode active material and the mass percentage of the second silicon-based material in the second negative electrode active material is 18-50%.
[0017] As a preferred technical solution of this disclosure, the first silicon-based material accounts for 80-100% of the mass percentage of the first negative electrode active material, and the first carbon-based material accounts for 0-20% of the mass percentage of the first negative electrode active material.
[0018] As a preferred technical solution of this disclosure, the second silicon-based material accounts for 50-72% of the mass percentage of the second negative electrode active material, and the second carbon-based material accounts for 28-50% of the mass percentage of the second negative electrode active material.
[0019] As a preferred technical solution of this disclosure, in the first negative electrode active material layer, the content of the first solid electrolyte is 10wt%-25wt%, the content of the first negative electrode active material is 70-90wt%, the content of the first conductive agent is 1wt%-5wt%, and the content of the first binder is 1wt%-5wt%.
[0020] As a preferred technical solution of this disclosure, by mass percentage, in the second negative electrode active material layer, the content of the second solid electrolyte is 10wt%-40wt%, the content of the second negative electrode active material is 55wt%-80wt%, the content of the second conductive agent is 1wt%-5wt%, and the content of the second binder is 1wt%-5wt%.
[0021] As a preferred technical solution of this disclosure, the total thickness of the first negative electrode active material layer and the second negative electrode active material layer is 40-80 μm.
[0022] As a preferred technical solution of this disclosure, the thickness ratio of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is (3-7):(7-3).
[0023] As a preferred technical solution of this disclosure, the first solid electrolyte and the second solid electrolyte each independently include a sulfide solid electrolyte; And / or, the first silicon-based material and the second silicon-based material each independently include one or more of silicon-carbon composite materials, elemental silicon, and silicon oxide materials; And / or, the first conductive agent and the second conductive agent each independently comprise a carbon material; And / or, the first adhesive and the second adhesive each independently comprise at least one of hydrogenated nitrile rubber, styrene-ethylene-butadiene-styrene block copolymer, and polyacrylic acid.
[0024] As a preferred technical solution of this disclosure, the particle size Dv50 of the first solid electrolyte and the second solid electrolyte is independently 0.3-1μm; And / or, the particle size Dv50 of the first silicon-based material and the second silicon-based material is independently 6-12 μm; And / or, the particle size Dv50 of the first carbon-based material and the second carbon-based material are each independently 5-15 μm, and the specific surface area is each independently 0.5-3 m² / g.
[0025] In a second aspect, this disclosure provides a solid-state battery, including a positive electrode, a solid electrolyte layer, and a negative electrode, wherein the negative electrode includes the negative electrode as described in the first aspect. The solid-state battery includes a solid-state lithium battery.
[0026] Thirdly, this disclosure provides a smart terminal, including the negative electrode sheet as described in the first aspect or the solid-state battery as described in the second aspect.
[0027] The technical solution provided in this disclosure has the following advantages compared with the prior art: (1) Volume expansion buffer: This disclosure provides a negative electrode with a double coating. The first negative electrode active material layer has a relatively high content of silicon-based material, which can provide high capacity. The second negative electrode active material layer has a relatively low content of silicon-based material and a relatively high content of carbon-based material. When the silicon-based material of the first negative electrode active material layer expands in volume, the second negative electrode active material layer can use the mechanical strength and high structural stability of the carbon-based material to provide stress buffer and disperse the expansion stress to a certain extent. (2) Optimization of ion transport and improvement of fast charging performance: The first negative electrode active material layer contains a relatively high content of silicon-based material, which provides sufficient ion transport path; the second negative electrode active material layer has a relatively high content of carbon-based material, and carbon-based material has excellent ion diffusion rate, which can realize fast charging and discharging. The two work together to achieve the matching of lithium ion flux and spatial position, and reduce local polarization. (3) Adjustment and balance of energy density and fast charging performance: This disclosure achieves different functional positioning by designing a gradient difference in the material content of the two layers. The first negative electrode active material layer contributes high capacity; the second negative electrode active material layer fully utilizes the advantages of fast charging, thereby achieving adjustment and balance between high energy density and excellent fast charging performance. Detailed Implementation
[0028] To better understand the above-mentioned objectives, features, and advantages of this disclosure, the solutions disclosed herein will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described herein can be combined with each other.
[0029] Numerous specific details are set forth in the following description in order to provide a full understanding of this disclosure, but this disclosure may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only some, and not all, of the embodiments of this disclosure.
[0030] In a first aspect, this disclosure provides a negative electrode sheet, including a negative electrode current collector, a first negative electrode active material layer disposed on at least one side of the negative electrode current collector, and a second negative electrode active material layer disposed on the side of the first negative electrode active material layer away from the negative electrode current collector. The first negative electrode active material layer includes a first solid electrolyte, a first negative electrode active material, a first conductive agent, and a first binder; the first negative electrode active material includes a first silicon-based material; The second negative electrode active material layer includes a second solid electrolyte, a second negative electrode active material, a second conductive agent, and a second binder; the second negative electrode active material includes a second silicon-based material and a second carbon-based material. The mass percentage of the first silicon-based material in the first negative electrode active material is greater than the mass percentage of the second silicon-based material in the second negative electrode active material.
[0031] This disclosure provides a negative electrode sheet with a double-layer coating, which achieves different functional positioning by designing a gradient difference in the material content of the two layers. Specifically: In one aspect, this disclosure provides a negative electrode sheet with a double-layer coating. The first negative electrode active material layer has a relatively high content of silicon-based material, which can provide high capacity. The second negative electrode active material layer has a relatively low content of silicon-based material and a relatively high content of carbon-based material. When the silicon-based material of the first negative electrode active material layer undergoes volume expansion, the second negative electrode active material layer can utilize the mechanical strength and high structural stability of the carbon-based material to provide stress buffer and disperse the expansion stress to a certain extent. Secondly, the first negative electrode active material layer contains a relatively high content of silicon-based materials, providing sufficient ion transport paths; the second negative electrode active material layer has a relatively high content of carbon-based materials, and carbon-based materials have excellent ion diffusion rates, enabling rapid charging and discharging. The two work together to achieve the matching of lithium ion flux and spatial position, reducing local polarization. Thirdly, this disclosure achieves different functional positioning by designing a gradient difference in the material content of the two layers. The first negative electrode active material layer contributes high capacity; the second negative electrode active material layer fully utilizes the advantages of fast charging, thereby achieving the adjustment and balance between high energy density and excellent fast charging performance.
[0032] In some embodiments, the first negative electrode active material further includes a first carbon-based material.
[0033] In some embodiments, the first carbon-based material and the second carbon-based material each independently comprise graphite.
[0034] In some embodiments, the difference between the mass percentage of the first silicon-based material in the first negative electrode active material and the mass percentage of the second silicon-based material in the second negative electrode active material is 18-50%, such as 18%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0035] In this disclosure, a reasonable difference in silicon-based material content helps stabilize the electrode structure during charging. If the difference is too large, it will also lead to excessive differences in charging expansion, resulting in layer slippage, electrode structure collapse, and cell degradation.
[0036] In some embodiments, the mass content of the first solid electrolyte in the first negative electrode active material layer is less than or equal to the mass content of the second solid electrolyte in the second negative electrode active material layer.
[0037] Preferably, the mass content of the first solid electrolyte in the first negative electrode active material layer is less than the mass content of the second solid electrolyte in the second negative electrode active material layer.
[0038] In some embodiments, the difference between the mass content of the second solid electrolyte in the second negative electrode active material layer and the mass content of the first solid electrolyte in the first negative electrode active material layer is 0-25%, such as 0, 5%, 10%, 15%, 20% or 25%, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0039] In this disclosure, the second negative electrode active material layer has a high content of solid electrolyte, which can further establish an efficient ion transport channel and reduce the ion transport impedance near the solid electrolyte layer. If the difference in the content of solid electrolyte is too large, it means that the difference in the content of negative electrode active material is too large, which in turn means that the difference in the content of silicon-based material is too large. Therefore, it will also lead to excessive differences in charging expansion, resulting in layer slippage, electrode structure collapse, and cell degradation.
[0040] In some embodiments, the first silicon-based material accounts for 80-100% of the mass percentage of the first negative electrode active material, such as 80%, 85%, 90%, 95%, or 100%; the first carbon-based material accounts for 0-20% of the mass percentage of the first negative electrode active material, such as 0%, 5%, 10%, 15%, or 20%, but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0041] In some embodiments, the second silicon-based material accounts for 50-72% of the mass percentage of the second negative electrode active material, such as 50%, 55%, 60%, 65%, 70%, or 72%; the second carbon-based material accounts for 28-50% of the mass percentage of the second negative electrode active material, such as 28%, 40%, 45%, or 50%, but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0042] In some embodiments, by mass percentage, the first solid electrolyte in the first negative electrode active material layer is 10wt%-25wt%, the first negative electrode active material is 70-90wt%, the first conductive agent is 1wt%-5wt%, and the first binder is 1wt%-5wt%.
[0043] The content of the first solid electrolyte can be 10wt%, 15wt%, 20wt%, or 25wt%, etc. The content of the first negative electrode active material is 70wt%, 75wt%, 80wt%, 85wt%, or 90wt%, etc.; The content of the first conductive agent can be 1wt%, 2wt%, 3wt%, 4wt%, or 5wt%, etc.; The content of the first binder can be 1wt%, 2wt%, 3wt%, 4wt%, or 5wt%, etc.; However, this does not limit the values listed; other unlisted values within the above range also apply.
[0044] In some embodiments, by mass percentage, the second negative electrode active material layer contains 10wt%-40wt% of the second solid electrolyte, 55wt%-80wt% of the second negative electrode active material, 1wt%-5wt% of the second conductive agent, and 1wt%-5wt% of the second binder.
[0045] The content of the second solid electrolyte can be 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, or 40wt%, etc. The content of the second negative electrode active material can be 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, or 80wt%, etc.; The content of the second conductive agent can be 1wt%, 2wt%, 3wt%, 4wt%, or 5wt%, etc.; The content of the second binder can be 1wt%, 2wt%, 3wt%, 4wt%, or 5wt%, etc.; However, this does not limit the values listed; other unlisted values within the above range also apply.
[0046] In this disclosure, a functionally graded bilayer structure is constructed by matching the appropriate content of solid electrolyte and the content of negative electrode active material for the first negative electrode active material layer and the second negative electrode active material layer. This alleviates the interface instability and stress fracture caused by the volume expansion of silicon-based materials to a certain extent, while taking into account both high energy density and excellent kinetic performance.
[0047] In some embodiments, the total thickness of the first negative electrode active material layer and the second negative electrode active material layer is 40-80 μm, such as 40 μm, 50 μm, 60 μm or 80 μm, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0048] In some embodiments, the thickness ratio of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is (3-7):(7-3), such as 3:7, 4:6, 5:5 or 7:3, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0049] Preferably, the thickness of the first negative electrode active material layer is equal to the thickness of the second negative electrode active material layer.
[0050] In this disclosure, the balance between energy density and fast charging performance can be adjusted by changing the thickness of the two active material layers. With the same composition ratio and total thickness, increasing the thickness of the first negative electrode active material layer can effectively improve energy density, but will weaken the fast charging advantage; increasing the thickness of the second negative electrode active material layer can effectively improve fast charging performance, but will sacrifice some energy density.
[0051] In some embodiments, the first solid electrolyte and the second solid electrolyte each independently comprise a sulfide solid electrolyte.
[0052] For example, the sulfide solid electrolyte includes, but is not limited to, Li6PS5Cl, Li 10 GeP2S 12 Li₂S-P₂S₅, Li₇P₃S 11 At least one of them, preferably Li6PS5Cl.
[0053] And / or, the first silicon-based material and the second silicon-based material each independently include one or more of silicon-carbon composite materials, elemental silicon, and silicon oxide materials.
[0054] The silicon-carbon composite materials include, but are not limited to, carbon-coated silicon-based composite materials and / or silicon-carbon composite materials in which silicon material is loaded in porous carbon.
[0055] And / or, the first conductive agent and the second conductive agent each independently comprise carbon materials.
[0056] For example, the carbon material includes, but is not limited to, at least one of fumed carbon fiber (VGCF), carbon nanotubes (CNT), and conductive carbon black, preferably VGCF.
[0057] In some embodiments, the first carbon-based material and the second carbon-based material each independently comprise natural graphite and / or artificial graphite, preferably artificial graphite.
[0058] And / or, the first adhesive and the second adhesive each independently comprise at least one of hydrogenated nitrile butadiene rubber (HNBR), styrene-ethylene-butadiene-styrene block copolymer (SEBS), and polyacrylic acid (PAA), preferably SEBS.
[0059] In some embodiments, the particle size Dv50 of the first solid electrolyte and the second solid electrolyte is independently 0.3-1 μm, such as 0.3 μm, 0.4 μm, 0.5 μm, 0.8 μm or 1 μm, but is not limited to the listed values. Other unlisted values within the above range are also applicable.
[0060] And / or, the particle size Dv50 of the first silicon-based material and the second silicon-based material is independently 6-12 μm, such as 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, etc., but is not limited to the listed values, and other unlisted values within the above range are also applicable.
[0061] And / or, the particle size Dv50 of the first graphite and the second graphite are each independently 5-15 μm, for example 5 μm, 8 μm, 10 μm, 12 μm or 15 μm, etc.; and the specific surface area is each independently 0.5-3 m². 2 / g, for example 0.5 m 2 / g、1 m 2 / g, 1.5m 2 / g、2 m 2 / g, 2.5m 2 / g or 3m 2 / g, compacted density is 1.5-1.8 g / cm³. 3 For example, 1.5g / cm 3 1.6g / cm 3 1.65g / cm 3 1.7g / cm 3 Or 1.8g / cm 3 The values listed are not limited to those listed; other unlisted values within the above range also apply.
[0062] In this disclosure, by screening suitable solid-state electrolytes, controlling the particle size distribution and structure of silicon-based materials, and matching graphite with specific particle sizes, the ion transport channels and electronic conductivity networks inside the electrode can be further synergistically optimized, thereby significantly improving the rate performance and cycle stability of the negative electrode. This multi-dimensional size and material matching can effectively alleviate the huge volume expansion during the lithium intercalation process of silicon-based materials, reduce internal resistance, and improve the kinetic characteristics of the electrode interface, ultimately enhancing the battery's fast charging capability and long service life at high energy densities.
[0063] Secondly, this disclosure provides a method for preparing a negative electrode sheet as described in the first aspect, the method comprising the following steps: (1) Dissolve the first solid electrolyte, the first silicon-based material, the first graphite, the first conductive agent and the first binder in the first solvent to obtain the first negative electrode slurry; coat the first negative electrode slurry on at least one surface of the negative electrode current collector, and after drying, form the first negative electrode active material layer; (2) The second solid electrolyte, the second silicon-based material, the second graphite, the second conductive agent and the second binder are dissolved in the second solvent to obtain the second negative electrode slurry; the second negative electrode slurry is coated on the surface of the first negative electrode active material layer, and after drying, the second negative electrode active material layer is formed to obtain the negative electrode sheet; Alternatively, S1, dissolve the first solid electrolyte, the first silicon-based material, the first graphite, the first conductive agent, and the first binder in a first solvent to obtain a first negative electrode slurry; dissolve the second solid electrolyte, the second silicon-based material, the second graphite, the second conductive agent, and the second binder in a second solvent to obtain a second negative electrode slurry; S2. Using a double-layer coating technique, the first negative electrode slurry and the second negative electrode slurry are coated onto at least one surface of the negative electrode current collector. After drying, a first negative electrode active material layer and a second negative electrode active material layer are formed to obtain a negative electrode sheet.
[0064] Thirdly, this disclosure provides a solid-state battery, including a positive electrode, a solid electrolyte layer, and a negative electrode, wherein the negative electrode includes the negative electrode as described in the first aspect; the solid-state battery includes a solid-state lithium battery.
[0065] Fourthly, this disclosure provides a smart terminal, including a negative electrode as described in the first aspect or a solid-state battery as described in the third aspect.
[0066] For example, the smart terminal includes, but is not limited to, vehicles, mobile computing devices (laptops, tablets), robots, drones, wearable smart devices (such as smartwatches, AR), medical devices, detection devices, etc.
[0067] The following explanation is provided through specific examples.
[0068] Unless otherwise specified, all raw materials used in the following examples are commercially available.
[0069] Example 1 This embodiment provides a negative electrode sheet and its preparation method, which includes a negative electrode current collector (copper foil, 10 μm thick), a first negative electrode active material layer (40 μm thick) respectively disposed on the upper and lower surfaces of the negative electrode current collector, and a second negative electrode active material layer (40 μm thick) disposed on the surface of the first negative electrode active material layer. By mass percentage, the first negative electrode active material layer comprises 15wt% of the first solid electrolyte (Li6PS5Cl, Tianshi Kefeng TS-01), 77wt% of the first silicon-based material (silicon-carbon composite material, BTR BSF-2), 6wt% of the first graphite (artificial graphite, Zichen GR-200), 1wt% of the first conductive agent (Showa Denko VGCF), and 1wt% of the first binder (SEBS, Keteng ly1500). By mass percentage, the second negative electrode active material layer comprises 30wt% of the second solid electrolyte (Li6PS5Cl, Tianshi Kefeng TS-01), 39wt% of the second silicon-based material (silicon-carbon composite material, BTR BSF-2), 29wt% of the second graphite (artificial graphite, Zichen GR-200), 1wt% of the second conductive agent (Showa Denko VGCF), and 1wt% of the second binder (SEBS, Keteng ly1500).
[0070] The combined specific capacity of the first negative electrode active material layer and the second negative electrode active material layer is 1106 mAh / g.
[0071] The preparation method includes: S1. Dissolve the first solid electrolyte, the first silicon-based material, the first graphite, the first conductive agent, and the first binder in the first solvent (butyl butyrate) to obtain the first negative electrode slurry; dissolve the second solid electrolyte, the second silicon-based material, the second graphite, the second conductive agent, and the second binder in the second solvent (butyl butyrate) to obtain the second negative electrode slurry; S2. Using a double-layer coating technology, the first negative electrode slurry and the second negative electrode slurry are coated onto the surface of the negative electrode current collector using a double-die extrusion coating machine. After drying (85°C), the first negative electrode active material layer and the second negative electrode active material layer are formed, thus obtaining the negative electrode sheet.
[0072] Specifically, the composition, content, and thickness of the first negative electrode active material layer and the second negative electrode active material layer are shown in Table 1.
[0073] Examples 2-14 and Comparative Examples 1-4 Examples 2-14 and Comparative Examples 1-4 respectively provide a negative electrode sheet and its preparation method. Referring to Example 1, the types of materials used in the first negative electrode active material layer and the second negative electrode active material layer remain unchanged. The specific composition and content and the thickness of the two layers are shown in Table 1.
[0074] Table 1
[0075]
[0076] Continued from Table 1
[0077]
[0078] It should be noted that the content of each component in Table 1 is by mass, in wt%.
[0079] Performance testing This disclosure provides a test battery, comprising: Negative electrode: The negative electrode described in Examples 1-14 and Comparative Examples 1-4 of this disclosure; Positive electrode sheet: The positive electrode active material (BASF NCM9 series), solid electrolyte (Li6PS5Cl, Tianshi Kefeng TS-01), conductive agent (Showa Denko VGCF), and binder (SEBS, Keteng ly1500) are mixed in a mass ratio of 78:20:1:1 and dissolved in butyl butyrate to obtain a positive electrode slurry; the positive electrode slurry is coated onto one surface of a 12μm thick aluminum foil and dried at 85℃ to form a positive electrode active material layer, thus obtaining a positive electrode sheet; wherein, the thickness of the positive electrode sheet is matched and adjusted according to the design areal capacity of the negative electrode so that the cell meets the requirement of a negative-to-positive electrode capacity ratio (N / P ratio) of 1.4; Solid electrolyte layer: Solid electrolyte (Li6PS5Cl, Tianshi Kefeng TS-01) and binder (SEBS, Keteng ly1500) are mixed at a mass ratio of 98:2 and dissolved in butyl butyrate to form a slurry; using the slurry, a solid electrolyte layer with a thickness of 110μm is prepared. The positive electrode, negative electrode, and solid electrolyte layer were assembled in an argon-filled glove box, and then pressed together under 500 MPa pressure to obtain the test battery. After standing for 4 hours, a charge-discharge test was performed.
[0080] 1. Ratio Performance Test ① Discharge to 2.5V at 0.05C, let stand for 5 minutes, then charge to 4.25V at 0.05C, repeat 4 times; ② Discharge to 2.5V at 0.05C, let stand for 5 minutes, then charge to 4.25V at 0.1C, repeat twice; ③ Discharge to 2.5V at 0.05C, let stand for 5 minutes, then charge to 4.25V at 0.05C, repeat twice; ④ Discharge to 2.5V at 0.05C, let stand for 5 minutes, then charge to 4.25V at 1C, repeat twice.
[0081] 2. Cyclic performance test ① Discharge to 2.5V at 0.05C, let stand for 5 minutes, then charge to 4.25V at 0.05C, repeat 4 times; ② Discharge to 2.5V at 0.1C, let stand for 5 minutes, then charge to 4.25V at 0.1C, repeat 500 times.
[0082] The test results are shown in Table 2.
[0083] Table 2
[0084] It should be noted that the overall specific capacity is calculated by weighting the theoretical specific capacity of the first and second negative electrode active material layers based on their respective formulations and the thickness ratio. Specifically, the theoretical specific capacity of each layer is calculated based on the mass fraction of silicon-based material (i.e., silicon-carbon composite material) and graphite in that layer and their respective specific capacities. The specific capacity of silicon-based material (i.e., silicon-carbon composite material) is set at 1800 mAh / g, and the specific capacity of graphite is set at 350 mAh / g.
[0085] As shown in Tables 1 and 2, the design of this application is conducive to achieving the adjustment and balance between energy density and fast charging performance.
[0086] Compared with Example 1, Comparative Example 1 has only one active material layer (the ratio of the active material layer is the same as that of the second negative electrode active material layer in Example 1), which results in a significant reduction in its specific capacity. Although its rate performance and cycle performance are better, they are still inferior to those of Example 1.
[0087] Compared with Example 1, Comparative Example 2 has only one active material layer (the ratio of the active material layer is the same as that of the first negative electrode active material layer in Example 1). Although it has a high specific capacity, it seriously affects its rate performance and cycle performance.
[0088] Compared with Example 1, the proportion of silicon-based material in the first negative electrode active material in Comparative Example 3 is less than that in the second negative electrode active material, resulting in a decrease in its rate performance and cycle performance.
[0089] Compared with Example 1, in Comparative Example 4, the mass content of the first solid electrolyte in the first negative electrode active material layer is greater than the mass content of the second solid electrolyte in the second negative electrode active material layer, which also leads to a decrease in its rate performance and cycle performance.
[0090] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0091] The above description is merely a specific embodiment of this disclosure, enabling those skilled in the art to understand or implement it. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this disclosure. Therefore, this disclosure is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A negative electrode sheet, characterized in that, It includes a negative electrode current collector, a first negative electrode active material layer disposed on at least one side of the negative electrode current collector, and a second negative electrode active material layer disposed on the side of the first negative electrode active material layer away from the negative electrode current collector. The first negative electrode active material layer includes a first solid electrolyte, a first negative electrode active material, a first conductive agent, and a first binder; the first negative electrode active material includes a first silicon-based material; The second negative electrode active material layer includes a second solid electrolyte, a second negative electrode active material, a second conductive agent, and a second binder; the second negative electrode active material includes a second silicon-based material and a second carbon-based material. The mass percentage of the first silicon-based material in the first negative electrode active material is greater than the mass percentage of the second silicon-based material in the second negative electrode active material.
2. The negative electrode sheet according to claim 1, characterized in that, The first negative electrode active material also includes a first carbon-based material.
3. The negative electrode sheet according to claim 1 or 2, characterized in that, The mass content of the first solid electrolyte in the first negative electrode active material layer is less than or equal to the mass content of the second solid electrolyte in the second negative electrode active material layer.
4. The negative electrode sheet according to any one of claims 1-3, characterized in that, The difference between the mass content of the second solid electrolyte in the second negative electrode active material layer and the mass content of the first solid electrolyte in the first negative electrode active material layer is 0-25%. And / or, the difference between the mass percentage of the first silicon-based material in the first negative electrode active material and the mass percentage of the second silicon-based material in the second negative electrode active material is 18-50%.
5. The negative electrode sheet according to any one of claims 1-4, characterized in that, The first silicon-based material accounts for 80-100% of the mass percentage of the first negative electrode active material, and the first carbon-based material accounts for 0-20% of the mass percentage of the first negative electrode active material. And / or, the second silicon-based material accounts for 50-72% of the mass percentage of the second negative electrode active material, and the second carbon-based material accounts for 28-50% of the mass percentage of the second negative electrode active material.
6. The negative electrode sheet according to any one of claims 1-5, characterized in that, By mass percentage, in the first negative electrode active material layer, the content of the first solid electrolyte is 10wt%-25wt%, the content of the first negative electrode active material is 70-90wt%, the content of the first conductive agent is 1wt%-5wt%, and the content of the first binder is 1wt%-5wt%. And / or, by mass percentage, in the second negative electrode active material layer, the content of the second solid electrolyte is 10wt%-40wt%, the content of the second negative electrode active material is 55wt%-80wt%, the content of the second conductive agent is 1wt%-5wt%, and the content of the second binder is 1wt%-5wt%.
7. The negative electrode sheet according to any one of claims 1-6, characterized in that, The total thickness of the first negative electrode active material layer and the second negative electrode active material layer is 40-80 μm; And / or, the thickness ratio of the first negative electrode active material layer to the thickness of the second negative electrode active material layer is (3-7):(7-3).
8. The negative electrode sheet according to any one of claims 1-7, characterized in that, The first solid electrolyte and the second solid electrolyte each independently comprise a sulfide solid electrolyte; And / or, the first silicon-based material and the second silicon-based material each independently include one or more of silicon-carbon composite materials, elemental silicon, and silicon oxide materials; And / or, the first conductive agent and the second conductive agent each independently comprise a carbon material; And / or, the first adhesive and the second adhesive each independently comprise at least one of hydrogenated nitrile rubber, styrene-ethylene-butadiene-styrene block copolymer, and polyacrylic acid; And / or, the particle size Dv50 of the first solid electrolyte and the second solid electrolyte is independently 0.3-1 μm; And / or, the particle size Dv50 of the first silicon-based material and the second silicon-based material is independently 6-12 μm; And / or, the particle size Dv50 of the first carbon-based material and the second carbon-based material are each independently 5-15 μm, and the specific surface area is each independently 0.5-3 m² / g.
9. A solid-state battery, comprising a positive electrode, a solid electrolyte layer, and a negative electrode, characterized in that, The negative electrode plate includes the negative electrode plate as described in any one of claims 1-8; The solid-state battery includes a solid-state lithium battery.
10. A smart terminal, characterized in that, Includes the negative electrode sheet as described in any one of claims 1-8 or the solid-state battery as described in claim 9.
Citation Information
Patent Citations
Negative plate, preparation method and solid-state battery
CN121687855A